The web application hacker's handbook : discovering and exploiting security flaws - Stuttard, Dafydd, 1972- (Wiley Pub., 2008)
This handbook offers a practical guide to discovering and exploiting security flaws in web applications. The authors explain each category of vulnerability using real-world examples, screen shots and code extracts.